2004
DOI: 10.1073/pnas.0305404101
|View full text |Cite
|
Sign up to set email alerts
|

Low acetylcholine during slow-wave sleep is critical for declarative memory consolidation

Abstract: The neurotransmitter acetylcholine is considered essential for proper functioning of the hippocampus-dependent declarative memory system, and it represents a major neuropharmacological target for the treatment of memory deficits, such as those in Alzheimer's disease. During slow-wave sleep (SWS), however, declarative memory consolidation is particularly strong, while acetylcholine levels in the hippocampus drop to a minimum. Observations in rats led to the hypothesis that the low cholinergic tone during SWS is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
217
4
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 356 publications
(245 citation statements)
references
References 41 publications
(46 reference statements)
22
217
4
2
Order By: Relevance
“…Sleep-dependent memory improvement in hippocampalrelated tasks appears to be reliant on SWS (Gais et al 2000). In particular, Gais and Born have demonstrated that low acetylcholine during SWS is important for explicit verbal memory (Gais et al 2004), but not implicit memory. Acetylcholine naturally decreases during sleep, whereas caffeine has been shown to increase hippocampal acetylcholine via antagonism of local adenosine A 1 receptors (Carter et al 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Sleep-dependent memory improvement in hippocampalrelated tasks appears to be reliant on SWS (Gais et al 2000). In particular, Gais and Born have demonstrated that low acetylcholine during SWS is important for explicit verbal memory (Gais et al 2004), but not implicit memory. Acetylcholine naturally decreases during sleep, whereas caffeine has been shown to increase hippocampal acetylcholine via antagonism of local adenosine A 1 receptors (Carter et al 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Third, the comparatively low level of sensory input experienced during SWS is an important way of minimising interference from external sources. Finally, the drastic reduction in acetylcholine that occurs during SWS, and that is essential for the transfer of information from hippocampal to neocortical memory stores [42], could also facilitate abstraction. Our proposal that SWS facilitates abstraction builds upon several influential theories of consolidation [14,17,34,43] which argue that slow waves assist the transfer of hippocampal memories to the neocortex (Box 2).…”
Section: Why Sleep?mentioning
confidence: 99%
“…Although consolidation of declarative, hippocampus-dependent memories of events and facts depends particularly on periods of SWS and on low cholinergic activity after learning (Marshall and Born, 2007;Gais and Born, 2004;Rasch et al, 2006), long-term acquisition of skills has been associated repeatedly with REM sleep after training , during which cholinergic tone regains wake-like levels. Numerous animal studies have shown that REM sleep is enhanced after learning of complex procedural tasks, and deprivation of REM sleep, by selective awakenings during certain time windows after learning, impairs subsequent task performance (see Smith, 1995;Peigneux et al, 2001, for a review).…”
Section: Introductionmentioning
confidence: 99%